2015
DOI: 10.1186/s12966-015-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in occupational sitting time in the Danish workforce and associations with all-cause mortality: results from the Danish work environment cohort study

Abstract: BackgroundProlonged sitting has been negatively associated with a range of non-communicably diseases. However, the role of occupational sitting is less clear, and little is known on the changes of occupational sitting in a working population over time. The present study aimed to determine 1) temporal changes in occupational sitting time between 1990 and 2010 in the Danish workforce; 2) the association and possible dose-response relationship between occupational sitting time and all-cause mortality.MethodsThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Many studies have shown that excessive sedentary behavior (SB) increases disease risk [1,2]. In this mechanized society, workers are particularly likely to be placed in sedentary situations in the workplace [3,4]. Therefore, workers' SB is an important risk factor for occupational health.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that excessive sedentary behavior (SB) increases disease risk [1,2]. In this mechanized society, workers are particularly likely to be placed in sedentary situations in the workplace [3,4]. Therefore, workers' SB is an important risk factor for occupational health.…”
Section: Introductionmentioning
confidence: 99%
“…In modern society, many people have office-based jobs entailing many hours of sitting [5] and hours spent sitting at work seems to be increasing [6]. Thus, occupational sitting has been the subject for much research interest lately [7].…”
Section: Introductionmentioning
confidence: 99%
“…Arbeitsplätze haben sich in den letzten Jahren verändert, immer mehr Beschäftigte verrichten vorwiegend sedentäre Tätigkeiten [13], gleichzeitig werden Zeitdruck und Arbeitsverdichtung wahrgenommen [14]. Sitzen am Arbeitsplatz unterscheidet sich von Sitzen in der Freizeit.…”
Section: Sitzen Am Arbeitsplatz -Sitzen In Der Freizeitgibt Es Untersunclassified